CHARACTERIZATION OF UJOGBA CLAY DEPOSITS IN EDO STATE, NIGERIA FOR REFRACTORY APPLICATIONS - Elakhame, Z; Bello, S. A.; Agunsoye, J. O.; Patric, I.; Otitoju, O. (Kathmandu University Journal of Science, Engineering and Technology, 2016)
Ujogba clay deposits in Esan Land, Edo State of Nigeria were characterized for refractory and other applications. The characteristics investigated were mineralogical composition, chemical composition, linear shrinkage, apparent porosity, bulk density, cold crushing strength and density. The physical property tests were carried out in accordance with ASTM C71. Results obtained showed that the Ujogba clays are largely kaolinite and chemically composed of mainly silica (68.93 %) and alumina (24.61 %). These oxides appreciated to 71.04 % (silica) and 19.63 % (alumina) in the fired product; yet the ratio of alumina to silica remained unchanged. The physical property such as refractory property examination confirmed that the clays belong to the fireclay class and are useful for refractory and ceramic applications. Kathmandu University Journal of Science, Engineering and Technology Vol. 12, No. 2, 2016, page: 71-82